CHARACTERIZE THE QUALITY OF COLOR, AROMA, TEXTURE AND TASTE OF COWPEA (Vigna unguiculata (L.) Walp.) TEMPEH FERMENTED BY DIFFERENT TYPES OF YEAST - Wardiah Wardiah; Samingan Samingan; Amelia Putri (BPFP Faperta UNIB, 2016)
Cowpea (Vigna unguiculata (L.) Walp.) has high content of nutrients and good source of phytoprotein. Therefore, it has potential opportunity to replace soybean in producing tempeh. The types of fermentation agent influence its quality, so it is crucial to study the use of types of tempeh yeast with different growt media in making cowpea tempeh. The study was aimed to characterize the quality of color, aroma, texture, and taste of cowpea tempeh fermented by different types of yeast. The method was experimental with complete random design, four treatments and six replicates. The parameter were physical quality; color, aroma, texture, and taste of tempeh. Data was collected by organoleptic test. Data was analysed using ANOVA at the 5 % significance level. The results showed that the preference levels of panelists differed against all parameters. Yeast utilizing cassava as its substrate produced cowpea tempeh with the highest preference level for all parameter.